Skeletal anchorage for intrusion of bimaxillary molars in a patient with skeletal open bite and temporomandibular disorders - Akihiko Iwasa; Shinya Horiuchi; Nao Kinouchi; Takashi Izawa; Masahiro Hiasa; Nobuhiko Kawai; Akihiro Yasue; Ali H Hassan; Eiji Tanaka (Wolters Kluwer Medknow Publications, 2017)
The treatment of severe skeletal anterior open bite is extremely difficult in adults, and orthognathic surgery is generally selected for its treatment. We report the case of an 18-year-old adult patient with skeletal anterior open bite and temporomandibular disorders who was successfully treated using temporary anchorage devices. She had an open bite of −2.0 mm and an increased facial height. Miniplates were implanted in both the maxilla and mandible, and molar intrusion resulted in counterclockwise rotation of the mandible over a period of 12 months. After active treatment, her upper and lower first molars were intruded by approximately 2 mm and her overbite became +2.5 mm. Her retrognathic profile improved with counterclockwise rotation of the mandible. Orthodontic treatment aided with skeletal anchorage is beneficial for intrusion of bimaxillary molars in patients with anterior open bite.